2008
DOI: 10.1016/j.mce.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the lutropin/choriogonadotropin receptor that do not activate the phosphoinositide cascade allow hCG to induce aromatase expression in immature rat granulosa cells

Abstract: Using primary cultures of immature rat granulosa cells and adenoviral infections we expressed two mutants of the human lutropin receptor (hLHR) that do not activate the phosphoinositide cascade. One mutant (hLFF) has the extracellular domain of the hLHR and the transmembrane and intracellular domains of the hFSHR. The other (hLHR-L457D) has a leucine to aspartate mutation in residue 457 of transmembrane helix 3.When expressed in immature rat granulosa cells the hLHR stimulates cAMP and inositol phosphate accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Whatever the origin of the LH increase in our PND4 mice, it appears to stimulate estrogen synthesis in the gonads, as E 2 content was significantly elevated in testes and ovaries from GABA B1 KO mice, with no alterations in T content. Although the natural stimulus for aromatase is FSH, it has been postulated that LH can induce aromatase synthesis and activity in various tissues, especially when LH receptors are present at low levels [66]. Alternatively, increased E 2 content in gonads of GABA B1 KO mice may be the consequence of the absence of local GABA B Rs, which are normally expressed in ovaries [67, 68] and testes [69], suggesting in this case that GABA B Rs may be negatively modulating aromatase synthesis and/or activity.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the origin of the LH increase in our PND4 mice, it appears to stimulate estrogen synthesis in the gonads, as E 2 content was significantly elevated in testes and ovaries from GABA B1 KO mice, with no alterations in T content. Although the natural stimulus for aromatase is FSH, it has been postulated that LH can induce aromatase synthesis and activity in various tissues, especially when LH receptors are present at low levels [66]. Alternatively, increased E 2 content in gonads of GABA B1 KO mice may be the consequence of the absence of local GABA B Rs, which are normally expressed in ovaries [67, 68] and testes [69], suggesting in this case that GABA B Rs may be negatively modulating aromatase synthesis and/or activity.…”
Section: Discussionmentioning
confidence: 99%
“…As summarized above, we reported its involvement in the regulation of Cyp19a1 expression as well as the release of epiregulin in primary cultures of rat granulosa cells (3)(4)(5), whereas others had previously described its role in cumulus expansion (12), oocyte meiotic resumption (12,13), and expression of some granulosa cell-specific genes (14,15). Recently, Richards and co-workers (16) generated a granulosa cell-specific deletion of ERK1/2 and showed that after LHR activation, the granulosa cells in these mice continue to proliferate and to express high levels of Cyp19a1 leading to an inappropriately high level of estradiol throughout the estrous cycle.…”
mentioning
confidence: 88%
“…Our previous studies using primary cultures of rat granulosa cells lead us to hypothesize that the EGFR is an important mediator of the LHR-stimulated decrease in ovarian Cyp19a1 expression (2)(3)(4)(5). We proposed that low gonadotropin receptor densities support Cyp19a1 expression because they activate pathways such as cAMP and AKT phosphorylation that enhance Cyp19a1 expression (6 -11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PIP3 recruits AKT to the membrane, promoting its phosphorylation. An elegant study by Andric and Ascoli using immature rat granulosa cells transfected with mutant LH receptors showed that LH-mediated AKT phosphorylation is independent of cAMP and inositol phopshate production (Andric and Ascoli 2008). PI3K may also be linked to activation of other effectors such as RAS (Ramjaun and Downward 2007).…”
Section: Lh Regulation Of Pi3-kinases and Downstream Pathwaysmentioning
confidence: 99%